Revisão Taxonômica e Relações Filogenéticas do Gênero Neotropical Ruptitermes Mathews, 1977 (Isoptera: Termitidae: Apicotermitinae) - Acioli, Agno Nonato Serrão (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
The taxonomy of the Neotropical termite genus Ruptitermes Mathews, 1977 (Isoptera: Termitidae: Apicotermitinae), is for the first time. This genus previously included 5 species: R. arboreus (Emerson), R. proratus Emerson, 1949, R. reconditus (Silvestri), R. silvestrii (Emerson) and R. xanthochiton Mathews, 1977. In this work, R. proratus is placed under the synonymy of R. reconditus, Anoplotermes franciscoi Snyder, 1959 is transferred to Ruptitermes, new combination, and 15 new species of Ruptitermes are described. Two identification keys to the species of Ruptitermes are presented, one based on imagos e other based on workers. New information on the geographic distribution and biology of the species is included. A cladistic analysis of 13 genera of Apicotermitinae and 6 genera of other groups, based on 92 morphological and biological characters, resulted in a single most parsimonious tree. The result indicates that Apicotermitinae is not a monophyletic group. The Neotropical genera Anoplotermes, Aparatermes, Ruptitermes from a clade close to Speculiltermes, a genus restricted to the Oriental Region. The genus Grigiotermes is not related to the other Neotropical Apicotermitinae, and seems to be closer to the African genera Amalotermes and Ateuchotermes. A second analysis was conducted incluing all 20 species of Ruptitermes and representatives of Apicotermitinae, using 43 morphological and biological characters. This analysis resulted in 3 most parsimonious trees, all showing good support for the monophyly of Ruptitermes, wiht 5 distinct synapormorphies.
Keywords: Cupins; Isoptera; Apicotermitinae